2019
DOI: 10.1186/s13063-019-3515-0
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing & Mobilizing the POtential for Wellness & Emotional Resilience (EMPOWER) among Surrogate Decision-Makers of ICU Patients: study protocol for a randomized controlled trial

Abstract: Background Critical illness increases the risk for poor mental health outcomes among both patients and their informal caregivers, especially their surrogate decision-makers. Surrogates who must make life-and-death medical decisions on behalf of incapacitated patients may experience additional distress. EMPOWER (Enhancing & Mobilizing the POtential for Wellness & Emotional Resilience) is a novel cognitive-behavioral, acceptance-based intervention delivered in the intensive care unit (ICU) setting t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…A common theme was that, although engaging in bereavement risk screening may be emotionally challenging, it could provide an opportunity to be connected to psychosocial support, even before bereavement; this is consistent with research demonstrating the utility of discussing bereavement pre‐loss to increase preparedness for the patient's death 30 . Many family members indicated they would prefer follow‐up after completing screening, with several preferring contact with a mental health professional.…”
Section: Discussionsupporting
confidence: 53%
“…A common theme was that, although engaging in bereavement risk screening may be emotionally challenging, it could provide an opportunity to be connected to psychosocial support, even before bereavement; this is consistent with research demonstrating the utility of discussing bereavement pre‐loss to increase preparedness for the patient's death 30 . Many family members indicated they would prefer follow‐up after completing screening, with several preferring contact with a mental health professional.…”
Section: Discussionsupporting
confidence: 53%
“…Given the most common regrets centered around treatment decision-making, greater emotional and decision-making support appears warranted. 60 It should not be assumed that parents who reach a decision are at peace with that decision. As the disease progresses, healthcare providers might take special care to explore decisions made thus far, providing reassurance, supporting coupled parents when their opinions may differ, and applying the “what if” framework to gently consider feared scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…Findings from a recent survey among the Canadian general population showed that most participants would support the introduction of a curriculum for senior high school students to learn about being an SDM, 31 further highlighting the need to develop and evaluate interventions that address the problem of a lack of preparedness to be an SDM in the general public. 44 In our study, a majority of participants preferred to obtain information from a health professional. This is consistent with a recent Australian study which found most people preferred to learn about end-oflife law from health professionals.…”
Section: Discussionmentioning
confidence: 92%